2018
DOI: 10.14715/cmb/2018.64.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Garlic (Allium sativum) and Thyme (Zataria multiflora Boiss) Extracts on Some Food Borne Pathogens and Their Effect on Virulence Gene Expression

Abstract: The incrementing scope of pathogenic resistance to antibiotics has encouraged the search for antivirulence natural extracts. Therefore, our study designed to demonstrate the antimicrobial activity of an aqueous-garlic and thyme oil extracts against Gram-positive (Staphylococcus aureus) and Gram-negative (Salmonella spp.) bacteria by evaluating the influence of sub-inhibitory concentrations on the expression of the most critical virulence genes of the tested isolates.The antibacterial potential of both herbs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The main compounds of the garlic oil used in the present study are diallyl disulfide and diallyl trisulfide. El-Azzouny et al (2018) demonstrated that aqueous garlic extract with its main compound allicin has a high antibacterial effect on Salmonella. Therefore, the differences in chemical composition, which resulted from different extraction procedures, may have high impact on the antibacterial efficacy of garlic extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The main compounds of the garlic oil used in the present study are diallyl disulfide and diallyl trisulfide. El-Azzouny et al (2018) demonstrated that aqueous garlic extract with its main compound allicin has a high antibacterial effect on Salmonella. Therefore, the differences in chemical composition, which resulted from different extraction procedures, may have high impact on the antibacterial efficacy of garlic extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of several bacterial enzymes such as trypsin and other proteases (Ifesan, Fadipe, & Ifesan, ) by allicin and other sulfur compounds has also been reported. Of these various reported compounds, allicin is the chief component (El‐Azzouny, El‐Demerdash, Seadawy, & Abou‐Khadra, ).…”
Section: Resultsmentioning
confidence: 99%
“…Later demonstrations of its action against cytomegalovirus [109] and infectious bronchitis virus are also worth consideration [110]. Being a good antimicrobial, it has depicted significant effect against staphylococcus aureus, E. coli, campylobacter jejuni, streptococcus mutans, lactobacillus acidophilus and salmonella species [111,112,113,114,115]. In an interesting study aged garlic was found to have more potent antioxidant and antimicrobial activities than fresh one [116].…”
Section: Garlic (Lehsun) (Allium Sativum)mentioning
confidence: 99%